Winding-number dependence of Bose-Einstein condensates in a ring-shaped lattice - Jezek, Dora Marta (2011)
We study the winding-number dependence of the stationary states of a Bose-Einstein condensate in a ring-shaped lattice. The system is obtained by confining atoms in a toroidal trap with equally spaced radial barriers. We calculate the energy and angular momentum as functions of the winding number and the barrier height for two quite distinct particle numbers. In both cases we observe two clearly differentiated regimes. For low barriers, metastable vortex states are obtained up to a maximum winding number that depends on the particle number and barrier height. In this regime, the angular momentum and energy show, respectively, almost linear and quadratic dependences on the winding number. For large barrier heights, on the other hand, stationary states are obtained up to a maximum winding number that depends only on the number of lattice sites, whereas energy and angular momentum are shown to be sinusoidal functions of the winding number. © 2011 American Physical Society.